2000
DOI: 10.1081/pdt-100100555
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Gel Formulations for Gene Delivery: Release and Myotoxicity Studies

Abstract: The in vitro release of plasmid DNA and salmon sperm DNA from in situ gel formulations was investigated. Two in situ gel systems were studied: (a) an interpolymeric complex (IPC) of water-soluble polymers polymethacrylic acid (PMA) and polyethylene glycol (PEG) and (b) a hydroxypropylmethylcellulose-carbopol system (H:C). Two-way analysis of variance with replication demonstrated that both gel composition and medium pH influenced significantly the release of plasmid DNA from in situ gel formulations. When the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Modified balance for determination of detachment force. DOI: 10.3109/10717544.2015.1065524 interfering with drug release (Ismail et al, 2000;Ismail, 2006). The gauze was fixed to the cup through a specially designed stainless steel ring.…”
Section: In Vitro Release Testing (Cup Method)mentioning
confidence: 99%
“…Modified balance for determination of detachment force. DOI: 10.3109/10717544.2015.1065524 interfering with drug release (Ismail et al, 2000;Ismail, 2006). The gauze was fixed to the cup through a specially designed stainless steel ring.…”
Section: In Vitro Release Testing (Cup Method)mentioning
confidence: 99%
“…For thê rst time, Yanger and Schoen described lipid microtubules made from the diacetylenic lipid 1,2-bis ( tricosa-10,12-diynoyl ) -sn-glycero-3-phosphocholine. 69,70) These microtubules are hollow and openended, with walls formed by one or more lipid bilayers. The chiral interactions between lipid molecules cause the bilayer to twist and form a tubular structure.…”
Section: Oil Suspensionsmentioning
confidence: 99%
“…Roy et al designed two ISG systems to modulate plasmid DNA release and gene expression for the delivery of DNA expression vectors and reported extended duration of expression after a single intramuscular administration [60]. In another study, the in vitro release of plasmid DNA and salmon sperm DNA from ISG formulations was investigated and the authors reported that ISG systems can be considered as a valuable injectable controlled delivery system for plasmid DNA in their role to provide protection from DNase degradation [61].…”
Section: Application In Vaccine and Gene Deliverymentioning
confidence: 99%